Faktor-Faktor Yang Berpengaruh Terhadap Nilai Perusahaan - Andi Jatmiko Suwarno, Liana Susanto (Jurnal Paradigma Akuntansi, 2021)
The purpose of this research is to obtain empirical evidence about the effects of capital structure, liquidity, financial performance and firm size on firm value of the manufacturing companies listed in the Indonesia Stock Exchange in the period of 2016-2018. The research is conducted by taking 74 samples using purposive sampling method. The result of this research shows that all the independent variables have effects on firm value  simultaneously (F test). The t test results showed that capital structure, financial performance  and firm size have positive significant effect on firm value, while liquidity has no significant effect on firm value (Tobin’s Q).